1999
DOI: 10.1002/(sici)1097-461x(1999)73:2<237::aid-qua17>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Computational approaches to the study of some lanthanide (III)-polyazamacrocyclic chelates for magnetic resonance imaging

Abstract: A set of parameters consistent with the CHARMM force field has been Ž . determined for molecular dynamics simulations of several DOTA᎐ and DOTP᎐Ln III chelates. Bonding and van der Waals parameters were derived from the available experimental data and analogy to similar ones in the existing force field. Net atomic charges were derived from ab initio calculations at the Hartree᎐Fock level to reproduce Ž . Ž . molecular electrostatic potentials ESPs , with an effective core potential ECP basis set for the metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…Notice that the guest structures are almost nonflexible (refer to the corresponding relatively small RMS values in table 3), as predicted by Henriques et al [23]. Consequently, the distances between the cyclodextrin hydroxyl groups and the chelate charged oxygens vary significantly under dynamic conditions, and that should account for most of the electrostatic energy fluctuations.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Notice that the guest structures are almost nonflexible (refer to the corresponding relatively small RMS values in table 3), as predicted by Henriques et al [23]. Consequently, the distances between the cyclodextrin hydroxyl groups and the chelate charged oxygens vary significantly under dynamic conditions, and that should account for most of the electrostatic energy fluctuations.…”
Section: Discussionsupporting
confidence: 64%
“…These particular structures, m 0 and M 0 , are meant to be analogous to the above referred m and M isomers respectively, but without the capping water molecule. Therefore, the [Tm(DOTP)] 5À m 0 structure was modelled [23], after the crystal structures of the complexes with the DOTP-like tetraalkyl-phosphinate ligands [22], DOTMP (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetramethylenemethylphosphinate) and DOTBzP (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetramethylenebenzylphosphinate), by substituting the four R groups (R Bz, Me) by the phosphonate oxygens in DOTP. The M 0 isomer was built based on the NMR structural results [8].…”
Section: Starting Geometriesmentioning
confidence: 99%
See 1 more Smart Citation
“…22−24 Complexes of related DOTAs (1,4,7,10-tetraazacyclododecane-N,N′,N″,N‴-tetraacetic acid) derivatives with Ln 3+ , although never applied as catalysts, have been widely used for in vivo luminescent probes 25−27 and MRI contrast agents, 28−35 and their structures and chemical properties have been studied both experimentally 28−35 and theoretically. 36,37 According to these studies, achiral Ln 3+ -DOTA has four stereoisomers, two pairs of enantiomers (as shown in Figure S1 in Supporting Information (SI)), and the existing probability of each conformer depends on Ln 3+ . Additionally, their chemical properties, such as the rate of water exchange on Ln 3+ , depend on the stereoisomers.…”
Section: ■ Introductionmentioning
confidence: 96%
“…Catalytic reactions in aqueous media have recently been one of the most important topics for green chemistry. Although conventional Lewis acid catalysts are inactive in water, a number of water-tolerant Lewis acid catalysts have been reported. Lanthanide (Ln) complexes fit into this group of catalysts. Ln trication (Ln 3+ ) catalysts were in fact used in the first report of aqueous C–C bond formation, the so-called Kobayashi modification of Mukaiyama-Aldol reaction, , and have been used in many aqueous reactions. Stereoselective reactions in aqueous media have also been reported with chiral ligands that are quite different from those widely used under anhydrous conditions. One of the distinct chiral ligands is crown ether derivatives. Allen and co-workers used the chiral complex of fluctional C 2 symmetric (2 R ,2′ R )-dialkyl 2,2′-(1,7-dioxa-4,10-diazacyclo­dodecane-4,10-diyl)­dipropanoates, abbreviated here as DODPs, and achieved highly enantio- and diastereoselective aqueous Mukaiyama-Aldol reaction between benzaldehyde and silyl enol ether, as shown in Scheme . Complexes of related DOTAs (1,4,7,10-tetraazacyclo­dodecane- N , N ′, N ″, N ‴-tetraacetic acid) derivatives with Ln 3+ , although never applied as catalysts, have been widely used for in vivo luminescent probes and MRI contrast agents, and their structures and chemical properties have been studied both experimentally and theoretically. , According to these studies, achiral Ln 3+ -DOTA has four stereoisomers, two pairs of enantiomers (as shown in Figure S1 in Supporting Information (SI)), and the existing probability of each conformer depends on Ln 3+ . Additionally, their chemical properties, such as the rate of water exchange on Ln 3+ , depend on the stereoisomers.…”
Section: Introductionmentioning
confidence: 99%